Extra-Territorial Ethnic Politics, Discourses and Identities in Hungary - Pogonyi, Szabolcs (Palgrave Macmillan, 2020)
Contents: Introduction.- Chapter 1: Citizenship and nation-building in post-Communist Central Eastern Europe.- Chapter 2: Kin-citizenship in the European context.- Chapter 3: Kin-citizenship in Hungary. From external minority protection to transborder nation building.- Chapter 4: Extraterritorial nation-building, inter-state relations and transboder minority mobilizaton in Hungary.- Chapter 5: Citizenship as a commitment: everyday perspectives on non-resident citizenship and voting rights in the Hungarian diaspora.- Conclusion.